PERWUDUJAN UPAYA PENEGAKAN HUKUM UNGGUL MENJADI IUS CONSTITUENDUM: BERKARAKTER BELA NEGARA DAN RELIGIUSITAS - Az Zanubiya, Siti Syafa; Afhdali, Dino Rizka; Triadi , Irwan (IBLAM LAW REVIEW, 2023)
Law Enforcement is a small part of legal development that continues to be pursued. This research uses qualitative data analysis method. The results of the study are then directed at the form of efforts to contribute to superior law enforcement towards ius constituendum and religiosity. The contribution of legal education is able to produce professional and virtuous jurists so as to realize superior Human Resources in the field of law to answer what has become a problem formulation in this study. This research uses a juridical-normative approach. Therefore, it emphasizes the study of library materials and the disclosure of the meaning of a positive legal norm. The data source used is secondary data, conducted through library research. In Islam, there are many statements about the rights and obligations of a Muslim in defending the homeland. On this basis, every Muslim defends the sovereign rights of his nation to achieve a country that is baldatun thoyyibatun wa robin ghofur.  Continuous efforts to develop the legal system are needed so that the law can play its role and function as a guide to behavior in living together